PEMBELAJARAN KIMIA TEMATIK PADA MATA KULIAH KIMIA DASAR SEBAGAI MODEL PEMBELAJARAN BERBASIS MASALAH - Sukisman Purtadi, Rr. Lis Permanasari & (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Thematic Chemistry Learning in the General Chemistry Course as a Problem-Based Learning Model. This study aims to investigate how thematic chemistry learning can be implemented and how the learning quality can be improved through thematic chemistry learning. This study was a quasiexperimental study. The participants were 49 students in the Chemistry Education Department attending the General Chemistry course. The focus was on the chemistry learning quality in terms of complex learning and information processing skill and students’ motivation and appreciation. The data were collected through observations and questionnaires. The results showed that the mean for complex learning and information process skills was 2.49 or in the good category. The mean of students’ motivation improved from 75.6 to 78.3 and the result of t-test was t = 9.39 (p = 0.000). Students’ appreciation varied; some showed positive appreciation and some showed negative appreciation. Keywords: thematic chemistry learning, problem based learning, learning quality